2016
DOI: 10.1021/acs.jpcb.5b10814
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Test of Reflectivity Formulas for Turbid Colloids: Beyond the Fresnel Reflection Amplitudes

Abstract: We compare light reflectivity measurements as a function of the angle of incidence for an interface between an optical glass and a turbid suspension of small particles, with theoretical predictions for the coherent reflectance calculated with different available theoretical models. The comparisons are made only in a small range of angles of incidence around the critical angle of the interface between the glass and the matrix of the colloidal suspensions. The experimental setup and its calibration procedure are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…Thus, in the current study, all the refractometric measurements were performed in the reflection mode. [58][59][60][61] The working principle of AR is based on the measurement of a critical angle. As it is shown in the inset of Fig.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…Thus, in the current study, all the refractometric measurements were performed in the reflection mode. [58][59][60][61] The working principle of AR is based on the measurement of a critical angle. As it is shown in the inset of Fig.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…The k lz , where l = i, j is the z-component of the wavenumber and takes the form of k lz = k o n 2 l − n 2 1 sin 2 θ 1 , where k o = 2π/λ is the wave number in a vacuum and λ is the wavelength. To calculate the reflectance of the entire system, the composed formula of reflectance [42] is needed which is defined as,…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The , where is the z -component of the wavenumber and takes the form of , where is the wave number in a vacuum and is the wavelength. To calculate the reflectance of the entire system, the composed formula of reflectance [ 42 ] is needed which is defined as, where d is the thickness of the thin film. To simulate the transmittance, the next expression is considered, where is the wavenumber in the effective medium, defined as where is the refractive index in each medium, is the angle of incidence, a is the radius of the particle, is the volume filling fraction, and is the forward-scattering amplitude of the NPs inside the matrix [ 44 ].…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The vdH EMM can be used in some cases to predict the reflectivity from turbid colloids of particles comparable to the wavelength of light. 26,30 However, in ref 25, it was shown that although an effective index of refraction can be properly defined in case the size of the colloidal particles is comparable or even larger than the wavelength of incident radiation, it is not strictly legitimate to use it, in these cases, in the calculation of Fresnel's reflection and transmission coefficients. 23−25 The use of the MG model is only justified when the size of the colloidal particles is very small with respect to the wavelength of the incident radiation, whether their absorption is important or not.…”
Section: Introductionmentioning
confidence: 99%